Bringing back our oceans - Hand, Carol, 1945- (Conservation success stories., 2018)
Examines the damage inflicted on the planet's oceans, their environmental importance, and the efforts being made to protect and restore them. Includes diagrams, a glossary, resources for further information, and color photographs.